The mechano-sensitivity of cardiac ATP-sensitive potassium channels is mediated by intrinsic MgATPase activity. (July 2017) - Fatehi, Mohammad; Carter, Christian C.; Youssef, Nermeen; Light, Peter E.
Abstract: Cardiac ATP-sensitive K + (KATP ) channel activity plays an important cardio-protective role in regulating excitability in response to metabolic stress. Evidence suggests that these channels are also mechano-sensitive and therefore may couple KATP channel activity to increased cardiac workloads. However, the molecular mechanism that couples membrane stretch to channel activity is not currently known. We hypothesized that membrane stretch may alter the intrinsic MgATPase activity of the cardiac KATP channel resulting in increased channel activation. The inside-out patch-clamp technique was used to record single-channel and macroscopic recombinant KATP channel activity in response to membrane stretch elicited by negative pipette pressure. We found that stretch activation requires the presence of the SUR subunit and that inhibition of MgATPase activity with either the non-hydrolysable ATP analog AMP-PNP or the ATPase inhibitor BeFx significantly reduced the stimulatory effect of stretch. We employed a point mutagenic approach to determine that a single residue (K1337) in the hairpin loop proximal to the major MgATPase catalytic site in the SUR2A subunit is responsible for the difference in mechano-sensitivity between SUR2A and SUR1 containing KATP channels. Moreover, using a double cysteine mutant substitution in the hairpin loop region revealed the importance of a key residue-residue interaction in this region that transduces membrane mechanical forces into KATP channel stimulation via increases in channel MgATPase activity. With respect to KATP channel pharmacology, glibenclamide, but not glicalizide or repaglinide, was able to completely inhibit KATP channel mechano-sensitivity. In summary, our results provide a highly plausible molecular mechanism by which mechanical membrane forces are rapidly converted in changes in KATP channel activity that have implications for our understanding of cardiac KATP channels in physiological or pathophysiological settings that involve increased workload. Graphical abstract: Highlights: Stretch-mediated activation of KATP channels requires the presence of the SUR subunit. Single residue accounts for differences in the stretch effect between SUR1 and SUR2A KATP channels. Stretch increases MgATPase activity via conformational changes in NBD2 structure. Only AB-site sulfonylurea inhibitors prevent the effects of stretch on KATP channel activity. Novel mechanism that may couple KATP channel activity to cardiac workload.